The Beneficial Role of Polysaccharide Hydrocolloids in Meat Products: A Review - Hanxiao Bao; Yuxi Wang; Yue Huang; Yuhao Zhang; Hongjie Dai (Gels)
Polysaccharide hydrocolloids have garnered increasing attention from consumers, experts, and food processing industries due to their advantages of abundant resources, favorable thickening properties, emulsification stability, biocompatibility, biodegradability, and high acceptance as food additives. This review focuses on the application of polysaccharide hydrocolloids and their beneficial roles in meat products by focusing on several commonly used polysaccharides (i.e., cellulose, chitosan, starch, sodium alginate, pectin, and carrageenan). Firstly, the recent advancements of polysaccharide hydrocolloids used in meat products are briefly introduced, along with their structure and potential application prospects. Then, the beneficial roles of polysaccharide hydrocolloids in meat products are comprehensively summarized and highlighted, including retarding lipid and protein oxidation, enhancing nutritional properties, improving texture and color quality, providing antibacterial activity, monitoring freshness, acting as a cryoprotectant, improving printability, and ensuring security. Finally, the challenges and opportunities of polysaccharide hydrocolloids in meat products are also introduced.